Role of tocilizumab therapy in COVID-19 patients: a systematic review - Srikumar, Shabarini; Muthiah, Aravind; Perumal, Shridharan (International Journal of Basic & Clinical Pharmacology, 2022)
Coronavirus disease 2019 (COVID-19) caused by the Severe acute respiratory syndrome coronavirus-2 (SARS CoV 2) virus has created a global threat to the entire human population. The medical and scientific community are striving hard to find an effective therapeutic strategy to overcome this crisis. There are few studies showing the efficacy of tocilizumab against COVID-19, but they many of them lack reliability due to their small sample size or sample population not representative of the general population. This meta-analysis aims to elucidate the role of tocilizumab in the management of COVID-19, its efficacy and safety profile. A comprehensive search of databases including PubMed, Medline, Cochrane, Lancet, Google Scholar, WHO, Embase, Elsevier and other modalities of search like website searching and citation tracking was carried out through which 1061 articles were identified. Among them, 10 articles that fitted the inclusion criteria and qualitatively good were taken up for the meta-analysis. Out of the 10 studies selected, the results of 9 studies were in favour of the efficacy of tocilizumab therapy, while 1 study was against the efficacy of tocilizumab. The result of our statistical analysis was that OR=0.5569 (95% CI; 0.2289 to 0.9332) for the effect of tocilizumab on mortality reduction in COVID-19 patients. Among critically ill patients with COVID-19, the in-hospital mortality was significantly reduced in patients treated with tocilizumab during the first 2 days of ICU admission compared to patients those who were not administered with tocilizumab in the early phase. Treatment with tocilizumab significantly reduces the mortality rate, increases the survival rate and lowers the risk of requiring invasive mechanical ventilation.